Redox Imbalance as a Common Pathogenic Factor Linking Hearing Loss and Cognitive Decline - Fabiola Paciello; Cristian Ripoli; Anna Rita Fetoni; Claudio Grassi (Antioxidants, 2023)
Experimental and clinical data suggest a tight link between hearing and cognitive functions under both physiological and pathological conditions. Indeed, hearing perception requires high-level cognitive processes, and its alterations have been considered a risk factor for cognitive decline. Thus, identifying common pathogenic determinants of hearing loss and neurodegenerative disease is challenging. Here, we focused on redox status imbalance as a possible common pathological mechanism linking hearing and cognitive dysfunctions. Oxidative stress plays a critical role in cochlear damage occurring during aging, as well as in that induced by exogenous factors, including noise. At the same time, increased oxidative stress in medio-temporal brain regions, including the hippocampus, is a hallmark of neurodegenerative disorders like Alzheimer’s disease. As such, antioxidant therapy seems to be a promising approach to prevent and/or counteract both sensory and cognitive neurodegeneration. Here, we review experimental evidence suggesting that redox imbalance is a key pathogenetic factor underlying the association between sensorineural hearing loss and neurodegenerative diseases. A greater understanding of the pathophysiological mechanisms shared by these two diseased conditions will hopefully provide relevant information to develop innovative and effective therapeutic strategies.